Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd003875.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix derivative (Emdogain®) for periodontal tissue regeneration in intrabony defects

Abstract: One year after its application, EMD significantly improved PAL levels (1.2 mm) and PPD reduction (0.8 mm) when compared to a placebo or control, however, the high degree of heterogeneity observed among trials suggests that results have to be interpreted with great caution. In addition a sensitivity analyses indicated that the overall treatment effect might be overestimated. The actual clinical advantages of using EMD are unknown. With the exception of significantly more postoperative complications in the GTR g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 52 publications
3
20
0
2
Order By: Relevance
“…EMD, obtained from porcine embryogenesis, is an amelogenin derivative (Hammarstrom 1997) that has been developed to promote periodontal regeneration. A systematic review on EMD has shown this regenerative potential in the treatment of intra‐bony defects (Esposito et al 2005) and an additional gain of clinical attachment has been shown when compared with open flap debridement alone (Esposito et al 2003, Pagliaro et al 2008, Sculean et al 2008). Less recession was found with EMD when compared with a guided tissue regeneration technique for the treatment of intra‐bony defects (Sculean et al 1999).…”
mentioning
confidence: 99%
“…EMD, obtained from porcine embryogenesis, is an amelogenin derivative (Hammarstrom 1997) that has been developed to promote periodontal regeneration. A systematic review on EMD has shown this regenerative potential in the treatment of intra‐bony defects (Esposito et al 2005) and an additional gain of clinical attachment has been shown when compared with open flap debridement alone (Esposito et al 2003, Pagliaro et al 2008, Sculean et al 2008). Less recession was found with EMD when compared with a guided tissue regeneration technique for the treatment of intra‐bony defects (Sculean et al 1999).…”
mentioning
confidence: 99%
“…In the last decade, the introduction of enamel matrix derivatives (EMD) in the treatment of periodontal lesions has led periodontal regeneration into a new era of tissue engineering. While its clinical efficacy is well established, little is known about the molecular mechanisms of its activities (Esposito et al 2005, Bosshardt 2008, Palmer et al 2008, Trombelli & Farina 2008). EMD has been received with great enthusiasm, and this has been shown in the numerous publications in the literature (Kalpitis & Ruben 2002, Venezia et al 2004, Esposito et al 2005).…”
mentioning
confidence: 99%
“…While its clinical efficacy is well established, little is known about the molecular mechanisms of its activities (Esposito et al 2005, Bosshardt 2008, Palmer et al 2008, Trombelli & Farina 2008). EMD has been received with great enthusiasm, and this has been shown in the numerous publications in the literature (Kalpitis & Ruben 2002, Venezia et al 2004, Esposito et al 2005). EMD has been used for treatments of periodontal lesions, such as furcation involvement (Hoffmann et al 2006) and infrabony defects (Esposito et al 2005, Tu et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of EMD has been first demonstrated in animal [10] and later in human studies [11]. Several systematic articles have systematically compared this approach to classical flap procedures and open debridement and have evaluated the additional benefit in the clinical outcomes [8, 12-14]. These reviews underline that EMD may exhibit a measurable positive clinical effect in combination with surgical treatment of periodontally diseased teeth when treating infrabony defects and furcations, provided that patients’ compliance is adequate and correct indications are pursued, including: careful assessment of defect depth, number of residual bony walls, pocket depth, and the degree of hypermobility.…”
Section: Discussionmentioning
confidence: 99%